ELASTIC ANISOTROPY OF PLAGIO-MIGMATITE CORE SAMPLES FROM KRYVORIZ’KA ULTRADEEP WELL: A PETROACOUSTIC INVESTIGATION - Bezrodnyi, D.; Tkachov, L.; Bezrodna, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
This paper investigates the influence of changes in the tectonic regime on the acoustic properties of plagio-migmatite samples from the Kryvoriz’ka ultradeep well based on petroacoustic analysis. The seismic-polarization method was used in the research to obtain velocities of longitudinal and transverse waves in nine directions. The velocity of plagio-migmatite core samples from Kryvoriz’ka ultradeep well an interval of 3,261–5,296 m have been defined with high accuracy. Based on petrophysical data, the authors obtained a full set of effective acoustic and elastic constants matrices and determined the parameters of anisotropy and rock texture types. It has been found that most of the samples exhibit an axial-rhombic type of texture symmetry. The integral anisotropy coefficient generally decreases with depth from 2,6 to 15 %, with the exception of cataclased plagio-migmatite. Analysis of anisotropy parameters showed that the depth interval 3,700–4,620 m is associated with the highest values of the integral coefficient of acoustic anisotropy, with the linear parameter significantly exceeding schistosity. From balanced velocity values there were obtained stereo-projections of directing surfaces of longitudinal wave propagation velocity, differences between "fast" and "slow" velocities of transverse waves and the differential coefficient of elastic anisotropy. Velocities of longitudinal waves at stereo-projections show less anisotropy than the other parameters. The difference between "fast" and "slow" transverse wave velocities for some samples (#16240 and #17725) is nearly 1 km/s, which suggests intensive elastic wave splitting in plagio-migmatites. The complexity and heterogeneity of elastic anisotropy is observed on stereo-projections of the differential anisotropy coefficient whose value ranges from 14 to 48 %. The number of extreme points on the stereo-projections of anisotropy parameters indicates significant heterogeneity of plagio-migmatite texture and changes as follows: Vp – 3,6, for the difference of transverse waves with different polarization – 6,14, Ad – 8,11. The parameters obtained are highly informative for research on the anisotropy of the medium. For samples #17010 and #19148 there are at least two extreme points where the nature of elastic wave propagation shows the medium to be isotropic, these are located at a 60 angle to the well axis. Research results show that the rocks from the well interval in question have been under high lateral compression. The type of acoustic tensor symmetry has little effect on reducing the anisotropy coefficient, which can be accounted for by an increase in pressure, and hence in density, with depth, the latter directly affecting the nature of rock anisotropy in the strata. Further research into the complex geological profile revealed by the Kryvoriz’ka ultradeep well should be based on a thorough petrographical and petrophysical analysis, with multidirectional anisotropy taken into account.